2022
DOI: 10.4103/ijo.ijo_1089_22
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination and recurrent anterior uveitis

Abstract: A 35-year-old Asian Indian female previously diagnosed with bilateral anterior uveitis and on oral methotrexate developed bilateral anterior uveitis following first/second dose of coronavirus disease 2019 (COVID-19) vaccination. She had skipped her weekly dose of oral methotrexate following first dose of vaccination. Following the second dose, she reduced her oral methotrexate from 25 to 15 mg on her own, but did not stop like the previous occasion. She had extensive workup for her uveitis in the past with onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…The authors postulated that COVID-19 or its vaccination may presumably play a role in triggering the immune system and can cause recurrent ocular inflammation even in the absence of an extra-ocular inflammation. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors postulated that COVID-19 or its vaccination may presumably play a role in triggering the immune system and can cause recurrent ocular inflammation even in the absence of an extra-ocular inflammation. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…Anterior uveitis has been reported to occur after coronavirus disease 2019 (COVID-19) and its vaccination. [ 1 - 8 ] Post-systemic viral infection can also cause anterior uveitis. We herein report a unique case who developed anterior uveitis after COVID-19, its vaccination, and dengue hepatitis.…”
mentioning
confidence: 99%
“…[ 60 ] The recent wave of COVID and the vaccination drive have also seen a rise in uveitis patients, especially anterior uveitis. [ 61 ] A retrospective observational study conducted at a tertiary eye care center in South India showed various presentations, including anterior, intermediate, posterior, and panuveitis in post-COVID-19 patients. [ 62 ] Following the pandemic, different vaccines were developed and approved by the main medical authorities under emergency protocol regulations.…”
Section: Advancements In Infective Uveitismentioning
confidence: 99%
“…The treating rheumatologist discussed the advantages and disadvantages of interrupting methotrexate to improve vaccine effectiveness, following available clinical guidance. 10 Subsequently, the patient chose to suspend immunosuppression for 2 doses of the vaccine.…”
Section: Case Reportmentioning
confidence: 99%
“…Ophthalmic manifestations have been reported following coronavirus disease (COVID-19) vaccine including episcleritis, scleritis, recurrent anterior uveitis, multifocal choroiditis, acute macular neuroretinopathy, paracentral acute middle maculopathy, vein occlusion, Vogt-Koyanagi-Harada disease (VKH), central serous chorioretinopathy (CSCR), herpes zoster re-activation or acute retinal necrosis. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] There are also reports of anterior uveitis occurring following 1st or 2nd dose of COVID-19 vaccination. 1,9 The current study discusses the case of a patient with recurrence of intraocular inflammation after COVID-19 vaccine after both first and second doses, and subsequently following the booster dose.…”
Section: Introductionmentioning
confidence: 99%